Формування і роль стереотипів в міжкультурній діловій комунікації - Гулівець, Н.О. (Культура народов Причерноморья, 2014)
Запропонована стаття присвячується дослідженню механізмів побудови культурних стереотипів у свідомості молодих фахівців в галузі міжнародної економіки. За допомогою методу анкетування та подальшої статистичної обробки даних були відслідковані асоціативні категорії і виділені ядерні та приядерні реакції, що формують культурні стереотипи «США», «Фінляндія» та «Колумбія». У роботі автор робить висновки про можливий вплив культурних стереотипів на процес ділового спілкування. Предлагаемая статья посвящается исследованию механизмов построения культурных стереотипов в сознании молодых специалистов в области международной экономики. При помощи метода анкетирования и последующей статистической обработки данных были отслежены ассоциативные категории и выделены ядерные и приядерные реакции, формирующие культурные стереотипы «США», «Финляндия» и «Колумбия». В работе автор делает выводы о возможном влиянии культурных стереотипов на процесс делового общения. Principles of equal partnership are widely recognized as the basis of international communication between nations and cultures. While engaged in this process, people develop ideas not only about their own culture, but about foreign cultures as well. Following Walter Lippmann, it is appropriate to call these ideas ‘stereotypes’. Stereotypes are formed and held as a result of cultural beliefs, practices, and traditions. When people hold stereotypes about others, they do not see them as individuals in their own sight, but in the light of pre-formed beliefs. The world is filled with stereotypes, and while they may provide some humor, they also give some guidance for interaction with others. While most stereotypes are universal, some are culture specific. The proposed paper answers the main question, “What is the stereotypical image of three countries – the USA, Finland, and Colombia?”, and is devoted to studying the mechanisms of constructing cultural stereotypes in minds of young professionals in the field of international economics. Using the method of questionnaire, the author collects the data and allots associative categories and nuclear and co-nuclear reactions that form the cultural stereotypes. In the end, the author draws conclusions about the possible effect of cultural stereotypes on the process of business communication.